Deep plasticity: The encoding approach to perceptual change. - Rollins, Mark (Philosophy of Science)
Argues that different kinds of perceptual plasticity have been confused in debates. Formulating the issues; Importance of plasticity-in-use; Parallel distributed processing; Generalized encoding approach; Fodor-Churchland debate.